Penurunan Fungsi Sistem Penghidu Pada Pasien Penyakit Parkinson: Epidemiologi dan Tatalaksananya - Agung Riatmojo, Andi (CV RIFAINSTITUT, 2022)
Parkinson's disease in general is a disorder of the central nervous system which most of its manifestations are motor function disorders. However, today's non-motor symptoms are found as early manifestations of Parkinson's disease. To determine the relationship between Parkinson's disease and non-motor symptoms, namely loss of smell or anosmia. The writing of this article includes various sources originating from scientific journals on online portals of journal publications such as MedScape, Google Scholar, PubMed, and NCBI, with the keywords